Festival Mangga sebagai Media Komunikasi dalam Mengoptimalkan Daya Tarik Wisata Desa Penggarit - Himawan Ardhi Ristanto; Adhi Iman Sulaiman; Shinta Prastyanti (Jurnal Ilmiah Komunikasi Makna, 2023)
Various tourism potentials exist in Penggarit Village, such as agricultural, religious, cultural, and natural educational tours. Mango has become the identity of Penggarit Village. Because this village is a producer of mangoes with the branding "Mangga Istana." Mango farming is a tradition (local wisdom) in the Penggarit village community. Almost every resident's house and garden have a mango tree. Penggarit Village seeks to increase tourism by holding a mango festival. The purpose of this study is to consider the Mango Festival as a communication media in the tourist attraction Pengarit Village. The research method used in this study is a qualitative method using case studies. The data in this study were generated through observation and interviews with informants. Four informants participated in this survey. Penggarit village chief, BUMdes director, Penggarit community chief, and Puskapik journalist. According to research results, Mango Festival is a cultural festival, flagship product festival, tourism village festival. This makes the mango festival a communication medium for Penggarit's tourist attraction. The composition of cultural attractions, natural resource attractions, and man-made attractions is mixed in such a way as to attract public interest. Beragam potensi wisata ada di Desa Penggarit, seperti wisata edukasi pertanian, religi, budaya dan alam. Mangga telah menjadi identitas Desa Penggarit. Sebab desa ini merupakan penghasil komoditas buah mangga unggul dengan branding â€œMangga Istanaâ€. Pertanian mangga sudah menjadi tradisi (Local Wisdom) bagi masyarakat Desa Penggarit. Hampir setiap rumah dan kebun warga memiliki pohon mangga. Desa Penggarit berupaya mengangkat daya tarik wisata dengan menyelenggarakan festival mangga. Tujuan dari penelitian ini adalah mengkaji festival mangga sebagai media komunikasi dalam mengoptimalkan daya tarik wisata Desa Penggarit. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif dengan menggunakan studi kasus. Data penelitian ini diperoleh melalui observasi dan wawancara dengan informan. Informan pada penelitian ini berjumlah empat orang, yaitu Kepala desa Penggarit, Direktur BUMDes Wiguna Utama, Tokoh Masyarakat Desa Penggarit dan Jurnalis Portal Berita Puskapik. Hasil penelitian, festival mangga merupakan festival budaya, festival produk unggulan dan festival desa wisata. Hal ini menjadikan Mango Festival sebagai sarana komunikasi objek wisata Penggrit. Komposisi daya tarik budaya, daya tarik sumber daya alam dan daya tarik buatan dipadukan sedemikian rupa sehingga menarik minat atau animo masyarakat.